Estruturas de acumulação de água subterrânea em rochas cristalinas: estudo geofísico e geológico de casos no Estado do Rio Grande do Norte - Silva, Jesimael Avelino da (2000)
Geological and geophysical studies (resistivity, self potential and VLF) were undertaken in the Tararaca and Santa Rita farms, respectively close to the Santo Antônio and Santa Cruz villages, eastern Rio Grande do Norte State, NE Brazil. Their aim was to characterize water acummulation structures in crystalline rocks. Based on geological and geophysical data, two models were characterized, the fracture-stream and the eluvio-alluvial through, in part already described in the literature. In the Tararaca Farm, a water well was located in a NW-trending streamlet; surrounding outcrops display fractures with the same orientation. Apparent resistivity sections, accross the stream channel, confirm fracturing at depth. The VLF profiles systematically display an alignment of equivalent current density anomalies, coinciding with the stream. Based on such data, the classical fracture-stream model seems to be well characterized at this place. In the Santa Rita Farm, a NE-trending stream display a metric-thick eluvioregolith-alluvial cover. The outcropping bedrock do not present fractures paralell to the stream direction, although the latter coincides with the trend of the gneiss foliation, which dips to the south. Geophysical data confirm the absence of a fracture zone at this place, but delineate the borders of a through-shaped structure filled with sediments (alluvium and regolith). The southern border of this structure dips steeper compared to the northern one. This water acummulation structure corresponds to an alternative model as regards to the classical fracture-stream, being named as the eluvio-alluvial trough. Its local controls are the drainage and relief, coupled with the bedrock weathering preferentially following foliation planes, generating the asymmetry of the through